Melatonin: biological significance and therapeutic properties - Rimšaitė, V.; Bogdanavičienė, K.; Gudavičiūtė, G.; Pajėdienė, E. (Neurologijos seminarai, 2022)
Melatonin is a hormone secreted by the pineal gland that is important for various neurological and endocrine processes in the body. With age and various diseases, a decrease in the concentration of melatonin is observed, its antioxidant effect is reduced, therefore, the circadian rhythm is disturbed, mental disorders occur, and the risk of oncological, neurodegenerative and cardiovascular diseases increases. Due to its wide spectrum of action, melatonin can be used successfully and safely for the prevention and treatment of various diseases. In recent years, the antineoplastic, anti-inflammatory, and analgesic effects of melatonin have been increasingly investigated, as has the potential positive effects of melatonin on adjuvant therapy for COVID-19 infection. By adapting the natural properties of melatonin for therapeutic purposes, exogenous melatonin preparations can potentially be used in addition to, or even as a substitute for, other currently used drugs. However, it is important to weigh the benefits and the risks. Although current studies show relative safety with low doses of exogenous melatonin, it is necessary to further investigate and analyze the safety and efficacy of these agents in the short and long term.
Keywords: melatonin; melatonin function; melatonin and aging; melatonin treatment; circadian rhythm; rhythm of sleep and alertness